RELATIONSHIP BETWEEN PROFESSIONAL MOBILITY AND COMPETENCIES IN PREPARING FOR THE FUTURE QUALIFIED WORKERS (Pedagogy of Higher and Secondary Education, 2022)
In article he auhor opens iportance preparanions professionally mobile qualiied worker on the baris of interrelation of professional mobility and competence.
Keywords: mobility; professional mobility; competence; qualified worker